Age-Related Patterns of Physical and Physiological Characteristics in Adolescent Wrestlers - Erkan Demirkan (Montenegrin Sports Academy, 2015)
The aim of the study was to examine the physical and physiological differences as dependent on age of young wrestlers. One hundred and twenty-six 15 - 17 year old wrestlers volunteered as subjects in the present study. The physical and physiological profiles included body weight, height, body mass index, flexibility, anaerobic power, aerobic endurance, strength, speed, and body composition. The statistically significant (p<0.05) results are as follows: Age group 17 (AG 17) had significantly higher leg and arm anaerobic power and capacity (leg power: 952±216 Watt (W); arm power: 684±194 W and leg capacity: 489±101 W; arm capacity: 354±88 respectively) as compared to the AG15 with (leg power: 718±279 Watt (W); arm power: 458±149 W and leg capacity: 376±132 W; arm capacity: 247±86 W respectively). AG17 wrestlers were significantly faster than AG 15 (4.29±.25 second - 4.53±.30 second respectively). AG 15 wrestlers had significantly lower right and left hand grip strength (right: 36.4±10.7 kg, left: 34.9±10 kg) than AG 16 (right: 43.9±8.4kg, left: 42.5±7.8 kg) and AG17 wrestlers (right: 46.6±8.7kg, left: 46.4±8.3 kg). In conclusion The results of this study suggest that height, body weight, fat free mass, arms - legs anaerobic power and capacity, speeds and hand grip strengths were increased both in one age range and in two ages range together with age progression, but it was clearly seen statistical differences in two ages range.